A Systematic review of factors affecting compliance toward oral iron-folic acid supplementation among pregnant women in India. - Khanam, Areeba; Vohra, Kashish; Achary MG, Thejas; Ranjith, Anjusha; Bharti, Harshiti; Rupam; Kaur, Ravneet; Yadav, Kapil (Indian Journal of Community Health, 2022)
Background: Iron-folic acid deficiency is the most common complication during pregnancy. Iron deficiency is responsible for various health complications among pregnant women. Compliance with IFA supplementation is variable across India several factors are associated with compliance with IFA supplementation. Objective: The objective of this systematic review is to assess the factors affecting compliance toward oral iron-folic acid supplementation among pregnant women in India. Methods: The primary search was carried out using PubMed, Google scholar, the WHO website, and Research Gate which provide access to full?text research articles from January 2012 to 25th January 2022 published data were searched. Result: A total of 74 studies were identified, and 20 were included in this review. Out of the 20 studies, sixteen were cross-sectional, two mixed methods, and two randomized control trials. knowledge of IFA, education, socioeconomic status, the timing of registration and number of antenatal visits, type of family, and age of the pregnant women were the factors that affect the compliance of IFA supplementation. Conclusion: Knowledge of iron-folic acid supplementation, Timing of registration and number of Antenatal Care visits, educational level of the pregnant women, and age of the pregnant women were factors associated with the compliance of IFA supplementation among pregnant women in India.